Relative costs of 24-hour recall and Household Consumption and Expenditures Surveys for nutrition analysis - Fiedler, John L.; Martin-Prével, Yves; Moursi, Mourad (SAGE Publications, 2013)
The technical and resource demands of the most precise dietary assessment methods, 24-hour recall and observed-weighed food records, have proven impractical for most low- and middle-income countries, leaving nutrition policymakers with a woefully inadequate evidence base and compromising nutrition program effectiveness.To better understand the relative costs of informing food and nutrition policy-making using two different data sources: 24-hour recall survey data and Household Consumption and Expenditures Survey (HCES) data.A comparative analysis of the costs of designing, implementing, and analyzing a 24-hour recall survey and the cost of secondary analysis of HCES data.The cost of conducting a 24-hour recall survey with a sample of the size typical of HCES would be roughly 75 times higher than the cost of analyzing the HCES data.Although the 24-hour recall method is undoubtedly more precise, it has become self-evident that the practical choice for most countries is not between these two surveys, but between having data from less precise, but much more readily available and affordable HCES or having no nationally representative data. In the light of growing concerns about inappropriate fortification policies developed without data, there is an urgent need to begin working to strengthen HCES to provide more precise food and nutrition data. The best way forward is not likely to rest with one data source or another, but with the development of an eclectic approach that exploits the strengths and weaknesses of alternative surveys and uses them to complement one another.